Immunomodulation mediated through Leishmania donovani protein disulfide isomerase by eliciting CD8+ T-cell in cured visceral leishmaniasis subjects and identification of its possible HLA class-1 restricted T-cell epitopes. Issue 1 (2nd January 2017) - Amit, Ajay; Dikhit, Manas R.; Mahantesh, Vijay; Chaudhary, Rajesh; Singh, Ashish Kumar; Singh, Ashu; Singh, Shubhankar Kumar; Das, V.N.R.; Pandey, Krishna; Ali, Vahab; Narayan, Shyam; Sahoo, Ganesh C.; et al.
Abstract : Protein disulphide isomerase (PDI) is one of the key enzymes essential for the survival of Leishmania donovani in the host. Our study suggested that PDI is associated with the generation of Th1-type of cellular responses in treated Visceral leishmaniasis (VL) subjects. The stimulation of Peripheral blood mononuclear cells (PBMCs) with recombinant Protein Disulphide Isomerase upregulated the reactive oxygen species generation, Nitric oxide release, IL12 and IFN-γ production indicating its pivotal role in protective immune response. Further, a pre-stimulation of PBMCs with Protein disulphide isomerase induced a strong IFN-γ response through CD8+ T cells in treated VL subjects. These findings also supported through the evidence that this antigen was processed and presented by major histocompatibility complex class I (MHC-1) dependent pathway and had an immunoprophylactic potential which can induce CD8+ T cell protective immune response in MHC class I dependent manner against VL. To find out the possible epitopes that might be responsible for CD8+ T cell specific IFN-γ response, computational approach was adopted. Six novel promiscuous epitopes were predicted to be highly immunogenic and can be presented by 32 different HLA allele to CD8+ T cells. Further investigation will explore more about their immunological relevance and usefulness as vaccine candidates.